Techno-Economic Optimization of a Grid-Tied Hybrid Photovoltaic–Battery System Under Vietnam Climatic Conditions - Tuan, Vu Trong; Kha, Cao Hoang; Minh, Nguyen Van (European Scientific Journal, ESJ, 2026)
The rapid growth of electricity demand in Vietnam has placed increasing pressure on the national power grid, highlighting the need for efficient renewable energy utilization. This study investigates the techno-economic performance of grid-connected photovoltaic– energy storage systems (PV–BESS) under Vietnam’s climatic conditions and electricity tariff structure. A detailed simulation framework is developed, incorporating PV generation, battery storage dynamics, inverter efficiency, and grid interaction. An energy management system (EMS) is implemented to coordinate power flows and evaluate three configurations: PV-only, PV+BESS, and PV+BESS with time-of-use (TOU)–based operation. Simulation results show that integrating battery storage significantly improves renewable energy utilization, increasing the self-consumption ratio (SCR) from 0.36 to 0.62 and the self-sufficiency ratio (SSR) from 0.40 to 0.68. The TOU-based strategy enhances operational flexibility by enabling tariff-driven energy shifting; however, it may increase grid import due to scheduled charging during off-peak periods. These findings highlight the trade-off between energy efficiency and economic optimization. Overall, hybrid PV–battery systems with appropriate energy management strategies represent a technically viable and economically attractive solution for improving renewable energy utilization in Vietnam.